Protection of water basin from contaminated water of sulphide - Butenko, Eleonora; Kapustin, Alexey (Technology audit and production reserves, 2014)
The processes of removal of sulfides are investigation. A technological setting is developed for the cleaning of natural and waste waters from sulfides.The aim of our research was to investigate the kinetics of removal of sulphides and development of technological systems for natural and waste waters from sulfides. Sulfides have a toxic effect on human and cause skin irritation. Hydrogen sulphide is toxic to living organisms. The toxicity of sulfide-ions is not so great as to cause acute poisoning, but prolonged use of water containing the substances in concentrations above the standard can develop chronic intoxication, leading ultimately to a particular disease. Note also that the toxic effects of substances can be shown not only by oral (by mouth) to receive them with water, but when absorbed through the skin in the process hygiene (shower, bath) or health (swimming pools) procedures. Also, the presence of sulfides in water (hydrogen sulfide) gives the water an unpleasant odor. At high concentrations of hydrogen sulfide a headache, dizziness, insomnia, weakness, cough. There is also a common neurotoxin effects. In scientific work carried out researches in area natural and waste waters from sulfide ions. Developed a working technological installation for natural and waste water from the sulphides. Optimized conditions for the removal of sulfide from wastewater